1996
DOI: 10.1289/ehp.961041172
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of polychlorinated terphenyls (PCTs) in indoor particulate matter.

Abstract: In the course of a routine investigation concerned with polychlorinated biphenyl (PCB) contamination of dust collected in classrooms of a junior high school, a group of electron capture detector (ECD)-sensitive compounds with high boiling points were found in addition to PCBs. Using gas chromatographic-mass spectrometric techniques, these compounds were identified as polychlorinated terphenyls (PCTs). Additional measurements indicated that the PCTs were present only in particulate matter collected from the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Recently, investigators have reported high concentrations of PCBs in dust associated with certain construction materials, such as caulking (Herrick et al, 2004) and wood floor finish , as well as with a PCB-contaminated fluorescent light ballast (Seidel et al, 1996) and a PCBcontaminated carpet pad (Franzblau et al, 2009). The prevalence of these particular PCB sources in residences is unknown; however, they are unlikely to be relevant in most homes.…”
Section: Determinants Of Pcb Levels In Residential Dustmentioning
confidence: 99%
“…Recently, investigators have reported high concentrations of PCBs in dust associated with certain construction materials, such as caulking (Herrick et al, 2004) and wood floor finish , as well as with a PCB-contaminated fluorescent light ballast (Seidel et al, 1996) and a PCBcontaminated carpet pad (Franzblau et al, 2009). The prevalence of these particular PCB sources in residences is unknown; however, they are unlikely to be relevant in most homes.…”
Section: Determinants Of Pcb Levels In Residential Dustmentioning
confidence: 99%
“…We also found that mother’s age was associated with concentrations of some PCBs in multivariable mixed-effects models after adjusting for home age. We speculate that older mothers (and fathers) are more likely to have owned PCB-contaminated consumer products manufactured before 1980, such as fluorescent lights, refrigerators, televisions, carpet pads, or air conditioners. ,− While most of these pre-1980 consumer items were likely removed from homes prior to dust collection, these items could have contaminated carpet dust or household surfaces, creating persistent PCB residues.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not identify specic items as PCB sources in this study, potential sources of PCBs in homes built before 1980 include PCB-contaminated consumer products, such as uorescent light ballasts, refrigerators, televisions, carpet pads, and air conditioners. [11][12][13]31 Based on the average lifetime of these products 17 (e.g. 20 year lifetime for a refrigerator), pre-1980 consumer items were likely removed from most homes prior to dust collection (2001)(2002)(2003)(2004)(2005)(2006).…”
Section: Discussionmentioning
confidence: 99%